Immediate Impact of Uni-nephrectomy among Bangladeshi Healthy Live Kidney Donors: BIRDEM General Hospital Experience (Journal of Enam Medical College, 2016)
Background: Kidney transplantation is the preferred treatment option for end stage kidney disease. Live kidney donation is an established form of organ donation; but it carries the risk of an unnecessary surgery in a normal individual. These donors remain at an increased risk of multiple medical problems for the rest of their life.Objective: In this study, we evaluated the immediate impact of uninephrectomy among kidney donors during the period of post-transplant hospital stay.Materials and Methods: This cross-sectional study was done at BIRDEM General Hospital from January 2006 to June 2014. All kidney donors who had undergone graft nephrectomy during the study period were the study population. All the donors underwent Tc-99m diethylene triamine pentaacetic acid (Tc-99m DTPA) renogram for measurement of glomerular filtration rate (GFR). GFR was also estimated by different equations in both pre-transplant and post-transplant periods. Pre-uninephrectomy GFR and post-uninephrectomy GFR of donors were compared.Results: Total number of subjects was 81, male 48 and female 33. Mean age was 36.3 ± 9.9 years. Mean postoperative hospital stay was 8.2 ± 2.0 days. The mean pre-operative measured glomerular filtration rate (mGFRDTPA) was 99.54 ± 19.06 mL/min/1.73 m2 and mean estimated glomerular filtration rate (eGFRCKD-EPI) was 99.0 ± 18.55 mL/min/1.73 m2 (p=0.855). In post-nephrectomy period mean urine output decreased from 2708.1 ± 842.8 to 2228.4 ± 702.4 mL/day (p=0.000). Mean SBP lowered from 120.3 ± 12.5 to 115.6 ± 9.2 mm of Hg (p=0.000) after nephrectomy. There was significant increase in blood urea (from 19.7 ± 5.7 to 30.4 ± 9.5 mg/dL, p=0.000) and serum creatinine (from 0.90 ± 0.16 to 1.26 ± 0.24 mg/dL, p=0.000) in post-uninephrectomy period. Mean mGFRDTPA of the subjects of non-nephrectomized kidney of the donors was 49.18 ± 9.50 mL/min/1.73 m2 and mean eGFRCKD-EPI of same kidneys was 69.09 ± 16.79 mL/min/1.73m2 (p=0.000) after uni-nephrectomy.Conclusion: Uninephrectomy in healthy adult kidney donors has immediate impacts on urine output, blood pressure, blood urea and serum creatinine levels.J Enam Med Col 2016; 6(2): 71-74